A super-hydrophobic porous organic cage-modified melamine sponge material and its preparation method and application
By combining the aldehyde-sylated cuvette [4]aromatic hydrocarbons and 2,2'-bis(trifluoromethyl)-[1,1'-biphenyl]-4,4'-diamine with melamine sponge, a superhydrophobic porous organic cage modified melamine sponge material was prepared, which solved the problem of strong hydrophilicity of melamine sponge in water-in-oil emulsion demulsification application, and achieved efficient demulsification of water-in-oil emulsion and excellent reusing performance of the material.
Patent Information
- Application Number
- CN202411896498.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-23
AI Technical Summary
The existing melamine sponges are highly hydrophilic in water-in-oil emulsion demulsification applications, making it difficult to effectively separate the oil phase, and have poor demulsification effects. The traditional demulsification methods are inefficient, costly, and risk of secondary pollution.
By combining the aldehyde-sylated cuvette [4]aromatics and 2,2'-bis(trifluoromethyl)-[1,1'-biphenyl]-4,4'-diamine with melamine sponge, a superhydrophobic porous organic cage modified melamine sponge material was prepared, and its superhydrophobicity and lipophilicity were used to achieve efficient emulsion demulsification of water-in-oil emulsion.
The material exhibits obvious superhydrophobicity and excellent reusable performance, which can quickly and efficiently demulsify, reduce production costs, reduce pollution, and has a stable material structure and is suitable for large-scale applications.
Smart Images

Figure CN119331304B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of materials, and in particular to a super-hydrophobic porous organic cage-modified melamine sponge material and a preparation method and application thereof. Background Art
[0002] In today's era of rapid industrial development, water-in-oil emulsions are widely used in many fields due to their unique properties. In oil extraction, it can improve crude oil recovery and help transport crude oil under complex geological conditions by stabilizing the emulsified state; in chemical production, it is often used as a reaction medium or product intermediate form, which is crucial to the smooth progress of the process; in the food processing industry, it can give food a unique taste and texture, and dairy products and sauces can achieve excellent quality in this way.
[0003] However, after the large-scale application of water-in-oil emulsions, subsequent treatment problems have become prominent, and demulsification has become a key difficulty. Traditional demulsification methods have obvious disadvantages. In terms of efficiency, it takes a long time to achieve demulsification and separation, which reduces the efficiency of large-scale industrial production processes and increases production cycles and costs. In terms of cost, a large amount of expensive chemical reagents or complex equipment may be required, resulting in high processing costs. What's more serious is that some traditional methods will produce secondary pollution. For example, chemical demulsifier residues may threaten the ecosystem, which is contrary to the concept of green environmental protection.
[0004] At the same time, the field of materials science focuses on developing special performance materials to meet diverse needs, which is a research hotspot. Melamine sponge has the advantages of light weight, porosity, and compressibility. Its light weight makes it easy to transport and operate, reducing energy consumption and labor costs; its porous structure provides abundant adsorption and reaction sites; and its compressibility adapts to special scenarios. However, the original melamine sponge is highly hydrophilic and has limitations in the application of demulsification of oil-in-water emulsions, because it preferentially reacts with the water phase in the emulsion, making it difficult to effectively separate the oil phase, resulting in poor demulsification effect.
[0005] Therefore, it is of great significance to modify melamine sponge to make it superhydrophobic. This can not only solve the problem of demulsification of oil-in-water emulsion, improve efficiency, reduce costs and reduce pollution, but also open up new application areas for melamine sponge, promote the coordinated development of materials science and related industrial fields, and provide technical support for the realization of efficient, environmentally friendly and sustainable industrial production models. It has extremely important research significance and broad application value, and is expected to play a key role in future industrial development and promote technological progress and sustainable development in various fields.
[0006] In order to improve the adsorption performance of melamine sponge and simplify the oil-water separation process, various materials are selected to modify melamine sponge in the prior art, including graphene, metal organic framework and hydrophobic polymer, etc. However, the preparation process of these modification technologies is complicated and expensive, making it difficult to achieve large-scale application. Summary of the invention
[0007] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a super-hydrophobic porous organic cage-modified melamine sponge material and a preparation method and application thereof. The material not only has obvious super-hydrophobicity, but also can efficiently demulsify water-in-oil emulsions and has excellent reusability, thereby expanding the application fields of porous materials and melamine sponges.
[0008] In order to achieve the above object, the technical solution adopted by the present invention is as follows:
[0009] A method for preparing a super-hydrophobic porous organic cage-modified melamine sponge material comprises the following steps:
[0010] Step (1), preparing a super-hydrophobic porous organic cage precursor solution;
[0011] The aldehyde-modified calix[4]arene and 2,2'-bis(trifluoromethyl)-[1,1'-biphenyl]-4,4'-diamine are mixed, N-methyl-2-pyrrolidone, chlorobenzene and methanol are added, and ultrasonic treatment is performed. After the treatment, a superhydrophobic porous organic cage precursor solution is obtained;
[0012] Step (2), preparing a super-hydrophobic porous organic cage-modified melamine sponge material;
[0013] The pretreated melamine sponge (MS) is immersed in a superhydrophobic porous organic cage precursor solution to react. After the reaction is completed, the MS is taken out and purified to obtain a superhydrophobic porous organic cage modified melamine sponge material (MS@POCs); wherein the purification includes extrusion, water washing, and drying.
[0014] Preferably, in step (1), the molar ratio of the aldehyde-modified calix[4]arene to 2,2'-bis(trifluoromethyl)-[1,1'-biphenyl]-4,4'-diamine is 1:2-3.
[0015] Preferably, in step (1), the volume ratio of N-methyl-2-pyrrolidone, chlorobenzene and methanol is 2:1:1-2.
[0016] Preferably, in step (1), the ultrasonic treatment time is 5-20 min.
[0017] Preferably, in step (2), the solid-to-liquid ratio of the pretreated melamine sponge to the superhydrophobic porous organic cage solution is 1:1-3.
[0018] Preferably, in step (2), the reaction conditions are: reacting at a temperature of 60-90° C. for 10-24 hours.
[0019] Preferably, in step (2), the pretreated melamine sponge is prepared by the following steps:
[0020] The melamine sponge was cut into blocks, placed in deionized water, and subjected to ultrasonic treatment. After the treatment, the sponge was taken out, transferred to ultrapure water, and subjected to ultrasonic treatment again. After the treatment, the sponge was taken out, squeezed, and dried to obtain the pretreated melamine sponge.
[0021] Furthermore, the ultrasonic treatment time is 10-20 min.
[0022] Furthermore, the conditions for the second ultrasonic treatment are: ultrasonic treatment again 1-2 times, each time for 10-20 minutes.
[0023] Preferably, a super-hydrophobic porous organic cage-modified melamine sponge material is prepared by the method for preparing a super-hydrophobic porous organic cage-modified melamine sponge material as described above.
[0024] Preferably, a melamine sponge material modified with the super-hydrophobic porous organic cage as described above is used in demulsification of water-in-oil emulsion.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] 1. In the present invention, formaldehyde-modified calix[4]arene and 2,2'-bis(trifluoromethyl)-[1,1'-biphenyl]-4,4'-diamine are selected as raw materials, and ultrasonically mixed in a solvent at a specific molar ratio to obtain a super-hydrophobic porous organic cage precursor solution, which is then composited with a melamine sponge to obtain a super-hydrophobic porous organic cage-modified melamine sponge material.
[0027] Among them, aldehyde-modified calix[4]arene has a unique cup-shaped structure. The distribution of its multiple aldehyde groups and the spatial structure of calixarene provide a good basis for constructing a complex and ordered organic cage structure, which can effectively control the reaction process and the structural morphology of the product; 2,2'-bis(trifluoromethyl)-[1,1'- [Biphenyl]-4,4'-diamine contains trifluoromethyl groups, which can not only enhance the stability of the molecule and maintain the integrity of the structure, but also give the organic cage compound excellent hydrophobic properties; the prepared porous organic cage compound has a relatively regular three-dimensional configuration with a certain cavity structure, which can be attached to the porous skeleton surface of the sponge through physical adsorption, and some residual active groups form covalent bonds with the melamine sponge. Through the synergistic effect of physical adsorption and chemical bonding, the organic cage compound can be stably and firmly loaded on the melamine sponge skeleton, forming a special surface structure that makes it difficult for water molecules to be stably adsorbed; at the same time, the organic cage compound has a highly ordered arrangement characteristic, which optimizes the distribution of hydrophobic groups and forms a continuous and efficient hydrophobic interface; the intrinsic superhydrophobicity and microstructure of the porous organic cage synergistically improve the superhydrophobic properties of the superhydrophobic porous organic cage-modified melamine sponge material, change the original hydrophilicity of the melamine sponge, and make it a hydrophobic and lipophilic composite material.
[0028] 2. Compared with the common demulsification materials currently available on the market, the super-hydrophobic porous organic cage-modified melamine sponge material prepared by the present invention has the advantages of high efficiency, rapid demulsification, easy material recovery and strong reusability, especially in the demulsification performance of oil-in-water emulsions.
[0029] 3. The super-hydrophobic porous organic cage-modified melamine sponge material prepared by the present invention has excellent reusability. This property is due to the stability of the material structure and the strong bonding between the porous organic cage compound and the melamine sponge, so that the material can still maintain good performance during multiple uses.
[0030] 4. The super-hydrophobic porous organic cage-modified melamine sponge material prepared by the present invention not only perfectly inherits the unique hydrophobicity advantage of the super-hydrophobic porous organic cage, but also retains the excellent properties of the melamine sponge such as light weight, porosity and compressibility. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 Schematic diagram of the synthesis of the super-hydrophobic porous organic cage-modified melamine sponge material prepared in the present invention;
[0032] Figure 2 This is a process flow chart for preparing a super-hydrophobic porous organic cage-modified melamine sponge material in the present invention;
[0033] Figure 3is the water contact angle of the super-hydrophobic porous organic cage-modified melamine sponge material prepared in Example 2 of the present invention;
[0034] Figure 4 is the water contact angle of the super-hydrophobic porous organic cage-modified melamine sponge material prepared in Example 3 of the present invention;
[0035] Figure 5 is the water contact angle of the super-hydrophobic porous organic cage-modified melamine sponge material prepared in Example 4 of the present invention;
[0036] Figure 6 is the water contact angle of the super-hydrophobic porous organic cage-modified melamine sponge material prepared in Example 5 of the present invention;
[0037] Figure 7 is the water contact angle of the super-hydrophobic porous organic cage-modified melamine sponge material prepared in Example 6 of the present invention;
[0038] Figure 8 is the water contact angle of the organic cage modified melamine sponge material prepared in Comparative Example 3 of the present invention;
[0039] Fig. 9 is the water contact angle of sample 1 prepared in Example 1 of the present invention;
[0040] Fig.10 is the water contact angle of sample 2 prepared by comparative example 2 in the present invention;
[0041] Fig.11 This is a comparison diagram of the appearance and hydrophilicity of the super-hydrophobic porous organic cage modified melamine sponge material prepared in Example 2 of the present invention and the pre-treated melamine sponge material prepared in Comparative Example 1;
[0042] Fig.12 is a scanning electron microscope comparison diagram of the super-hydrophobic porous organic cage modified melamine sponge material prepared in Example 2 of the present invention and the pre-treated melamine sponge material prepared in Comparative Example 1;
[0043] Fig.13 This is the EDS spectrum of the super-hydrophobic porous organic cage modified melamine sponge material prepared in Example 2 of the present invention;
[0044] Fig.14 It is the FT-IR spectrum of the super-hydrophobic porous organic cage prepared in Example 1 of the present invention, the super-hydrophobic porous organic cage modified melamine sponge material prepared in Example 2, and the pretreated melamine sponge material prepared in Comparative Example 1;
[0045] Fig.15It is a thermogravimetric analysis spectrum of the super-hydrophobic porous organic cage modified melamine sponge material prepared in Example 2 of the present invention and the pretreated melamine sponge material prepared in Comparative Example 1;
[0046] Fig.16 is a schematic diagram of the demulsification device in the experimental data characterization and performance tests 7 and 8 of the present invention;
[0047] Fig.17 It is a schematic diagram of the demulsification principle in the experimental data characterization and performance tests 7 and 8 of the present invention;
[0048] Fig.18 It is a comparison effect diagram of the appearance of the toluene-in-water emulsion without stabilizer before and after demulsification in the experimental data characterization and performance test 7 of the present invention;
[0049] Fig.19 It is a comparison effect diagram of the appearance of the cyclohexane water-in-water emulsion without stabilizer before and after demulsification in the experimental data characterization and performance test 7 of the present invention;
[0050] Fig. 20 The experimental data characterization and performance test 8 of the present invention are the appearance comparison effect diagram and microscopic picture comparison diagram of the toluene-in-water emulsion with the stabilizer added before and after demulsification;
[0051] Fig.21 This is a comparison effect diagram of the appearance of the cyclohexane water-in-water emulsion with the stabilizer added before and after demulsification in the experimental data characterization and performance test 8 of the present invention;
[0052] Fig. 22 is the water contact angle of the super-hydrophobic porous organic cage modified melamine sponge material prepared in Example 2 of the present invention after repeated demulsification experiments for 15 times;
[0053] Fig.23 This is a comparison diagram of the appearance changes of the super-hydrophobic porous organic cage-modified melamine sponge material prepared in Example 2 of the present invention after continuous compression and pressing for 50 times;
[0054] In the figure:
[0055] Fig.11 a is the pretreated melamine sponge material prepared in Comparative Example 1; b is the super-hydrophobic porous organic cage-modified melamine sponge material prepared in Example 2;
[0056] Fig.12 a and c are the pretreated melamine sponge materials prepared in Comparative Example 1, and b and d are the super-hydrophobic porous organic cage-modified melamine sponge materials prepared in Example 2. DETAILED DESCRIPTION
[0057] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0058] A method for preparing a super-hydrophobic porous organic cage-modified melamine sponge material comprises the following steps:
[0059] Step (1), preparing a super-hydrophobic porous organic cage precursor solution;
[0060] 21 mg of aldehyde-modified calix[4]arene and 10 mg of 2,2'-bis(trifluoromethyl)-[1,1'-biphenyl]-4,4'-diamine were mixed, 4 mL of N-methyl-2-pyrrolidone, 2 mL of chlorobenzene, and 2 mL of methanol solvent were added, and ultrasonic treatment was performed for 15 min. After the treatment, a superhydrophobic porous organic cage precursor solution was obtained;
[0061] Step (2), preparing a pretreated melamine sponge;
[0062] The melamine sponge was cut into blocks of 2 cm×2 cm×2 cm, placed in deionized water, and ultrasonically treated for 10 min. After the treatment, the sponge was taken out, transferred to ultrapure water, and ultrasonically treated again for 2 times, each time for 10 min. After the treatment, the sponge was taken out, squeezed, and dried in an oven at 65° C. for 5 h to obtain the pretreated melamine sponge.
[0063] Step (3), preparing a super-hydrophobic porous organic cage-modified melamine sponge material;
[0064] The pretreated melamine sponge (MS) was immersed in a superhydrophobic porous organic cage precursor solution with a solid-liquid ratio of 1:1-3, and reacted at 60-90°C for 10-24h. After the reaction, the reacted melamine sponge was taken out, the excess emulsion was squeezed out, and the melamine sponge was washed thoroughly with deionized water and dried at 60°C for 6h to obtain a superhydrophobic porous organic cage modified melamine sponge material (MS@POCs).
[0065] Example 1
[0066] The super-hydrophobic porous organic cage precursor solution is prepared by adopting step (1) of the method for preparing a super-hydrophobic porous organic cage-modified melamine sponge material as described above.
[0067] Example 2
[0068] The super-hydrophobic porous organic cage-modified melamine sponge material was prepared by the method for preparing the super-hydrophobic porous organic cage-modified melamine sponge material as described above, wherein in step (3) of this embodiment, the solid-liquid ratio is 1:1.5, and the reaction conditions are 80° C. for 18 hours.
[0069] Example 3
[0070] The difference from Example 2 is that the solid-liquid ratio in step (3) is changed to 1:2, the reaction conditions are changed to reacting at 60° C. for 14 h, and the other parameters and conditions are the same as those in Example 2.
[0071] Example 4
[0072] The difference from Example 2 is that the solid-liquid ratio in step (3) is changed to 1:2.5, the reaction conditions are changed to reacting at 75° C. for 20 h, and the other parameters and conditions are the same as those in Example 2.
[0073] Example 5
[0074] The difference from Example 2 is that the solid-liquid ratio in step (3) is changed to 1:3, the reaction conditions are changed to reacting at 80° C. for 20 h, and the other parameters and conditions are the same as those in Example 2.
[0075] Example 6
[0076] The difference from Example 2 is that the solid-liquid ratio in step (3) is changed to 1:3, and the other parameters and conditions are the same as those in Example 2.
[0077] Comparative Example 1
[0078] The difference from Example 2 is that step (1) and step (3) are omitted, and other parameters and conditions are the same as those in Example 2.
[0079] Comparative Example 2
[0080] The difference from Example 1 is that the formaldehyded calix[4]arene is changed to 2,4,6-triformylphloroglucinol, 2,2'-bis(trifluoromethyl)-[1,1'-biphenyl]-4,4'-diamine is changed to diphenyl diamine, and the solvent is changed to 1 mL N-methyl-2-pyrrolidone, 1.5 mL chlorobenzene, and 3 mL methanol. The other parameters and conditions are the same as those in Example 1.
[0081] Comparative Example 3
[0082] The difference from Example 2 is that the formaldehyde-modified calix[4]arene in step (1) is changed to 2,4,6-triformylphloroglucinol, 2,2'-bis(trifluoromethyl)-[1,1'-biphenyl]-4,4'-diamine is changed to diphenyl diamine, and the volume ratio of N-methyl-2-pyrrolidone, chlorobenzene and methanol is changed to 1 mL:1.5 mL:3 mL; the solid-liquid ratio in step (3) is changed to 1:3, and the reaction conditions are changed to react at 75°C for 20 h. Other parameters and conditions are the same as those in Example 2.
[0083] In the above examples and comparative examples: the aldehyde calix[4]arene was prepared in-house, and specifically included the following steps: 33 g of resorcinol (30 mmol), 285 mL of ethanol and 15 mL of water were mixed, stirred at 15° C. for 10 min, 75 mL of concentrated hydrochloric acid was added, 25.8 g of isovaleraldehyde (30 mmol) was slowly added dropwise in an ice-water bath, after the addition was complete, the oil bath was heated to 65° C., and the reaction was continued for 12 h. After the reaction was complete, the precipitate was filtered out, washed with a small amount of cold ethanol, and vacuum dried to obtain resorcinol calix[4]arene; 6 g of resorcinol calix[4]arene, 8 g of hexamethylenetetramine, and 50 mL of trifluoroacetic acid were mixed, stirred and heated in an oil bath at 120° C. for 8 h, after the reaction was completed, cooled to room temperature, 250 mL of chloroform and 250 mL of 1 mol / L hydrochloric acid aqueous solution were added, and the mixture was rapidly stirred for 12 h. h, separate the liquids, extract with chloroform several times, take the organic phase, and rotary evaporate to obtain a crude product. The crude product is washed with acetone, filtered, and vacuum dried at 60°C to obtain aldehyded calix[4]arene;
[0084] 2,2'-Bis(trifluoromethyl)-[1,1'-biphenyl]-4,4'-diamine was purchased from Shanghai Bid Pharmaceutical Technology Co., Ltd. The molecular formula is C 14 H 10 F6N2, CAS number: 341-58-2.
[0085] Experimental data characterization and performance testing
[0086] 1. Water contact angle test:
[0087] like Figure 3-7 As shown, the water contact angles of the materials prepared in Examples 2-6 and Comparative Example 3 were measured respectively, and the specific test results are shown in Table 1:
[0088] Table 1
[0089] Example 2 Example 3 Example 4 Example 5 Example 6 Comparative Example 3 Water contact angle (°) 142 114 123 118 129 91.82
[0090] According to Table 1 and Figure 3-7The test data clearly show that under different synthesis conditions, the water contact angles of the super-hydrophobic porous organic cage-modified melamine sponge material prepared in the embodiments of the present invention show differences.
[0091] Porous organic cages (POCs) are a class of discrete, covalently bonded molecular structures with built-in cavities that can be accessed by guest molecules, which endow them with porous properties. Their shape and size can be tuned by changing the synthetic raw materials and reaction conditions.
[0092] The present invention soaks the pretreated melamine sponge in a super-hydrophobic porous organic cage precursor solution and reacts at a specific temperature of 60-90°C. During the reaction, when the organic cage compound contacts the melamine sponge, on the one hand, the organic cage compound may be attached to the porous skeleton surface of the sponge through physical adsorption. This is because the melamine sponge has a rich pore structure, and these pores provide a large number of attachment sites for the organic cage. The organic cage can interact with the sponge skeleton through intermolecular forces (such as van der Waals forces); on the other hand, from the perspective of chemical bonding, the aldehyde cup[4] Some active groups remaining on the aromatic hydrocarbons (such as incompletely reacted aldehyde groups or hydroxyl groups) may undergo further chemical reactions with functional groups such as amino groups on the melamine sponge to form covalent bonds. The synergistic effect of this physical adsorption and chemical bonding enables the organic cage compound to be stably and firmly loaded on the melamine sponge skeleton, and it is not easy to fall off even under interference from the external environment or mechanical action during use, thereby ensuring the stability and durability of the prepared superhydrophobic porous organic cage-modified melamine sponge material.
[0093] During the reaction process, the reaction temperature will affect the growth rate and crystallinity of the organic cage on the melamine sponge. At a specific temperature, the synthesis reaction rate of the organic cage is moderate, which can ensure the integrity and functionality of its structure. At the same time, the combination reaction with the sponge can proceed smoothly, promoting the formation of a stable connection structure between the organic cage and the sponge, and enhancing the overall stability and hydrophobicity of the material; too high a temperature may cause the organic cage to grow too fast, crystallize unevenly, partially destroy the organic cage structure or be too loosely combined with the sponge, resulting in inconsistent roughness of the microstructure on the surface of the material; too low a temperature may result in incomplete reaction, and the organic cage cannot fully grow and load on the melamine sponge.
[0094] Different solvents have different solubility for reactants, which will affect the uniformity and reactivity of the reaction system. Solvents with stronger polarity can promote the formation of certain chemical bonds, while solvents with weaker polarity are conducive to the self-assembly process of organic cages. In terms of reactant concentration, too high a concentration can easily lead to agglomeration, resulting in uneven distribution of organic cages on the surface of the material and the formation of defects. Too low a concentration will reduce the chance of effective collisions, reduce the generation of organic cages and loading efficiency. These synthetic conditions combined will affect the morphology of the microstructure of the material surface and the distribution of chemical composition, thereby changing the interaction mode and effect between the material and water in terms of macroscopic performance.
[0095] In addition, sufficient and appropriate reaction time can ensure that the growth, assembly and interaction of the organic cage on the sponge reach a saturated and stable state, so that the microstructure of the material is optimized, thereby maximizing the hydrophobic effect. The difference in reaction time in the embodiments may cause the growth and binding process of the organic cage on the sponge to terminate prematurely or proceed excessively, resulting in structural defects or unstable performance of the material, and ultimately causing its hydrophobic performance to be inferior to that of the best embodiment.
[0096] Compared with the material prepared in Comparative Example 3, the reason why Examples 2-6 have advantages is that Comparative Example 3 uses the porous organic cage precursor solution prepared in Comparative Example 2. In Comparative Example 2, the aldehyde monomer used is 2,4,6-triformylphloroglucinol, which is different from the aldehyde-modified calix[4]arene used in Example 1 to prepare the superhydrophobic porous organic cage precursor solution. 2,4,6-triformylphloroglucinol has a relatively high reactivity. In the process of synthesizing organic cages, it is easy to form a random polymer network structure, but it is difficult to accurately control the generation of organic cages with specific structures and sizes. The formed organic cage structure is relatively simple and has poor regularity. It lacks the unique cup-shaped structure and multi-aldehyde distribution characteristics of aldehyde-modified calix[4]arene, and it is difficult to construct a highly ordered and complex organic cage structure. As a result, after it is modified on the melamine sponge, it cannot effectively form a microscopic rough structure and a low surface energy interface that are conducive to hydrophobic properties. At the same time, in Comparative Example 2, 2,4,6-triformylphloroglucinol and the fluorine-free amino compound diphenyl diamine are used to prepare the precursor solution. The formed organic cage structure lacks sufficient effective hydrophobic groups. It cannot reduce the surface energy of the material well after modifying the melamine sponge like the organic cages in Examples 2-6, thereby causing the material prepared in Comparative Example 3 to have poor hydrophobic properties.
[0097] like Fig. 9 and Fig.10 As shown, the porous organic cage precursor solutions prepared in Example 1 and Comparative Example 2 were reacted at 80° C. for 18 h, and after post-treatment, porous organic cage (POCs) powders were obtained, which were recorded as Sample 1 and Sample 2. The water contact angles of Sample 1 and Sample 2 were measured respectively. The specific test results are shown in Table 2:
[0098] Table 2
[0099] Sample 1 Sample 2 Water contact angle (°) 157.3 113.9
[0100] According to Table 2 and Figure 8 It can be seen from the test results that the sample 1 prepared in Example 1 has excellent hydrophobic properties, and the water contact angle is as high as 157.3°, showing super hydrophobic properties. This is because the porous organic cage prepared in the present invention has a unique microstructure and chemical composition. From the perspective of microstructure, there are abundant micropores and cavity structures inside it. These pores form a complex surface roughness, so that when water droplets contact the surface of the material, they cannot spread and infiltrate, but are supported by the pores to form a similar "air cushion". The effect of greatly reducing the actual contact area between water and materials; from the perspective of chemical composition, organic cage molecules contain a large number of special hydrophobic groups, such as long-chain alkyl groups and trifluoromethyl groups. Long-chain alkyl groups have lower surface energy and can effectively reduce the interaction energy between water molecules and the surface of the material, making the water molecules more inclined to self-aggregate and leave the surface of the material; the fluorine-containing groups, due to their high electronegativity and special electron cloud distribution, further enhance the repulsion of the material to water molecules. These hydrophobic groups are orderly arranged or enriched on the surface of the material. When water molecules approach, a strong repulsive effect is generated between the hydrophobic groups and the water molecules. The water molecules are more inclined to aggregate with each other and maintain their own shape, making it difficult to penetrate into the interior of the material, thereby making the material exhibit superhydrophobic properties.
[0101] In the sample 2 prepared in comparative example 2, since the aldehyde monomer used in comparative example 2 is 2,4,6-triformylphloroglucinol, the organic cage structure formed is relatively simple and has poor regularity, lacking the unique cup-shaped structure and multi-aldehyde group distribution characteristics like aldehyde-formyl calix[4]arene, it is difficult to construct a highly ordered and complex organic cage structure, resulting in the inability to effectively form a microscopic rough structure and low surface energy interface that are conducive to hydrophobic performance. At the same time, comparative example 2 uses an aldehyde monomer containing 2,4,6-triformylphloroglucinol and diphenyl diamine to prepare the precursor solution, and the organic cage structure formed lacks sufficient effective hydrophobic groups, so the hydrophobic performance of sample 2 prepared in comparative example 2 is poor compared with sample 1 prepared in example 1.
[0102] 2. If Fig.11 As shown, the super hydrophobic porous organic cage modified melamine sponge material prepared in Example 2 and the pretreated melamine sponge material prepared in Comparative Example 1 were compared in appearance and hydrophilicity;
[0103] according to Fig.11It can be seen from the test results that the pretreated melamine sponge material prepared in Comparative Example 1 has an adsorption effect on both oil and water, while the appearance color of the super-hydrophobic porous organic cage modified melamine sponge material prepared in Example 2 changes from the initial white color of the melamine sponge to light red. It can be seen from the test of the water contact angle that Example 2 has obvious hydrophobic and oleophilic properties. This is because in the present invention, the super-hydrophobic porous organic cage is attached to the melamine sponge by a specific synthesis and loading method. From the microscopic structure, the porous organic cage forms a special modification layer in the pores and surface of the sponge. Its unique three-dimensional structure increases the roughness of the material surface, making it difficult for water droplets to spread on its surface. From the perspective of chemical composition and interaction, the porous organic cage molecules have hydrophobic groups. When these hydrophobic groups come into contact with water, due to their low affinity with water molecules and relatively high affinity with oil molecules, they will cause water molecules to aggregate with each other to form water droplets and roll down, while oil molecules are more likely to come into contact with the material surface and be adsorbed. At the same time, there is chemical bonding or strong physical adsorption between the porous organic cage and the melamine sponge, which ensures the stability and durability of the hydrophobic and lipophilic properties, so that the material as a whole exhibits obvious hydrophobic and lipophilic properties. The appearance color also changes from white to light red due to the loading of the porous organic cage, and the water contact angle shows obvious hydrophobic characteristics.
[0104] 3. If Fig.12 As shown, a scanning electron microscope comparison test was performed on the super hydrophobic porous organic cage modified melamine sponge material prepared in Example 2 and the pretreated melamine sponge material prepared in Comparative Example 1;
[0105] according to Fig.12 It can be seen from the test results that compared with Example 2, many tiny grains of porous organic cages grow inside the super-hydrophobic porous organic cage-modified melamine sponge material prepared in Example 2, which proves that the super-hydrophobic porous organic cage grows inside the melamine sponge material and is loaded smoothly, which is the key to the source of the hydrophobicity of the super-hydrophobic porous organic cage-modified melamine sponge.
[0106] 4. If Fig.13 As shown, the EDS spectrum of the super hydrophobic porous organic cage modified melamine sponge material prepared in Example 2 is characterized; (a) distribution of C element, (b) distribution of N element, (c) distribution of O element, (d) distribution of F element, (e) energy spectrum analysis of each element of MS@POCs;
[0107] According to the characterization results in Figure 13, the distribution of the F element can be observed. This phenomenon shows that in the super-hydrophobic porous organic cage modified melamine sponge material, the fluorine element is uniformly present in the overall structure of the material. On the one hand, the presence of the fluorine element indicates the successful preparation of the composite material. On the other hand, the fluorine element is of great significance to the material performance. Its unique electronegativity and atomic structure characteristics help to enhance the hydrophobic properties of the material. Through the special interaction with water molecules and the regulation of the surface energy of the material, the composite material can effectively repel water molecules, thereby showing super-hydrophobic properties, and establishes a close connection between the microstructure and macroscopic properties of the material, which provides a key basis and clues for further understanding and research on the relationship between the structure and performance of the material.
[0108] 5. If Fig.14 As shown, the materials prepared in Example 1, Example 2 and Comparative Example 1 were characterized by FT-IR spectra;
[0109] according to Fig.14 It can be seen from the characterization results that compared with Comparative Example 1, the super-hydrophobic porous organic cages (POCs) prepared in Example 1 and the super-hydrophobic porous organic cage modified melamine sponge material (MS@POCs) prepared in Example 6 have a higher hydrophobicity at 1582 cm -1 New peaks were observed at 1265 cm -1 The peak can be attributed to CF stretching vibration; the above results all confirm that 2,2'-bis(trifluoromethyl)-[1,1'-biphenyl]-4,4'-diamine successfully reacts with aldehyde-modified calix[4]arene to generate superhydrophobic porous organic cages, and that the superhydrophobic porous organic cages are smoothly loaded on the melamine sponge skeleton to form superhydrophobic porous organic cage-modified melamine sponge materials.
[0110] 6. If Fig.15 As shown, the materials prepared in Example 2 and Comparative Example 1 were characterized by thermogravimetric analysis (TGA);
[0111] like Fig.15 As shown, the pretreated melamine sponge material (MS) prepared in Comparative Example 1 and the superhydrophobic porous organic cage modified melamine sponge (MS@POCs) prepared in Example 2 showed a continuous mass loss of about 20% in the range of room temperature to 382°C; when the temperature exceeded 382°C, both Example 2 and Comparative Example 1 showed rapid mass loss, which may be caused by framework decomposition. These experimental results strongly prove that the loading of superhydrophobic porous organic cages does not change the excellent thermal stability of melamine sponge, and both melamine sponge and superhydrophobic porous organic cage modified melamine sponge have excellent thermal stability.
[0112] 7. Demulsification test of water-in-oil emulsion without stabilizer:
[0113] like Figure 18-19 As shown, the materials prepared in Examples 2-6 and Comparative Example 1 were used as demulsifying materials to perform a demulsification test of an oil-in-water emulsion without a stabilizer. The specific operation process is as follows:
[0114] The materials prepared in Examples 2-6 and Comparative Example 1 were used as filling materials to assemble into Fig.16 The device shown; slowly pour the oil-in-water emulsion without stabilizer into the top of the device, and after a few seconds, observe the state of the solution flowing out from the bottom of the device.
[0115] The stabilizer-free water-in-oil emulsion is prepared by the following steps:
[0116] The water phase and the oil phase were mixed in a volume ratio of 1:100, the oil phase was toluene and cyclohexane, and ultrasonic treatment was performed for 6 hours to obtain a stabilizer-free toluene-in-water emulsion and a stabilizer-free cyclohexane-in-water emulsion, respectively.
[0117] according to Figure 18-19 It can be seen from the test results that the appearance of the emulsion before and after demulsification shows a clear difference. The emulsion without demulsification is milky white, and the emulsion after demulsification becomes a clear and transparent solution; the principle of traditional demulsification materials is the phase transfer-reverse deformation principle, which is to add an oil-soluble demulsifier (opposite to the emulsion type) to form a complex with a hydrophobic emulsifier, so that the emulsifier loses its emulsifying properties and demulsifies, which may take several hours to complete the demulsification process. The super-hydrophobic porous organic cage-modified melamine sponge material prepared by the present invention can achieve the same or even better demulsification effect in just a few minutes. The principle is that the material prepared by the present invention has hydrophobic and lipophilic properties. In addition to the suction force on the oil phase, it also has a repulsive force on the water phase. The synergistic effect of the two enables the super-hydrophobic porous organic cage-modified melamine sponge material prepared by the present invention to achieve fast and efficient demulsification.
[0118] 8. Demulsification test of water-in-oil emulsion with stabilizer added:
[0119] like Figure 20-21 As shown, the materials prepared in Examples 2-6 and Comparative Example 1 were used as demulsifying materials to carry out demulsification test of water-in-oil emulsion with stabilizer, and the specific operation process was as follows:
[0120] The materials prepared in Examples 2-6 and Comparative Example 1 were used as filling materials to assemble into Fig.16 The device shown; slowly pour the oil-in-water emulsion with added stabilizer into the top of the device, and after a few seconds, observe the state of the solution flowing out from the bottom of the device.
[0121] The water-in-oil emulsion with added stabilizer is prepared by the following steps:
[0122] The water phase and the oil phase were mixed in a volume ratio of 1:100, the oil phase was toluene and cyclohexane, and the stabilizer Span-80 was added in an amount of 20% of the mass of the water phase. Ultrasonic treatment was performed for 6 hours to obtain a toluene-in-water emulsion with added stabilizer and a cyclohexane-in-water emulsion with added stabilizer, respectively.
[0123] according to Figure 20-21 The test results show that the appearance of the emulsion before and after demulsification is significantly different. The undemulsified emulsion is milky white, while the emulsion after demulsification becomes a clear and transparent solution. Under a microscope, obvious water droplets can be observed in the undemulsified emulsion, but not after demulsification.
[0124] In oil-in-water emulsions, stabilizers play a vital role; stabilizers are usually some surfactant substances, and their molecular structure has hydrophilic groups and hydrophobic groups; in the oil-in-water emulsion system, the hydrophobic group of the stabilizer will extend to the oil phase, and the hydrophilic group will interact with the water phase, thus forming a stable interfacial film at the oil-water interface. This interfacial film can reduce the surface tension of the oil-water interface, prevent the mutual collision and aggregation between oil droplets, and enable the emulsion to maintain a stable dispersion state. For example, some common emulsifiers such as sodium dodecyl sulfate can stably disperse tiny water droplets in the oil phase by forming an interfacial film in the oil-in-water emulsion, preventing the water droplets from merging into large water droplets due to mutual contact and causing emulsion stratification.
[0125] There are some technical difficulties in the existing demulsification technology of oil-in-water emulsions with added stabilizers. Traditional demulsification methods, such as adding oil-soluble demulsifiers and hydrophobic emulsifiers to form complexes to break the emulsion, often take a long time to destroy the stable interface film formed by the stabilizer and demulsify the emulsion. This is because the interaction between traditional demulsifiers and stabilizers is relatively slow and complex, and the stable structure of the emulsion needs to be gradually destroyed, so it may take two hours to complete the demulsification process; and for some special stabilizers or complex emulsion systems, traditional demulsification technology may be difficult to completely remove the influence of the stabilizer, resulting in poor demulsification effect.
[0126] The super-hydrophobic porous organic cage modified melamine sponge material prepared by the present invention can overcome these problems. First, the super-hydrophobic property of the material enables it to quickly repel the water phase when it contacts the emulsion, prompting water droplets to gather on the surface of the material. Due to the special microstructure and low surface energy of the material surface, water droplets cannot stably exist on its surface, but tend to merge with each other to form larger water droplets; at the same time, the lipophilic property of the material enables it to adsorb the oil phase. In the process of adsorbing the oil phase, it will produce a pulling and destructive effect on the interfacial film formed by the stabilizer at the oil-water interface. This pulling effect is due to the synergistic production of the material's adsorption force on the oil phase and the repulsion force on the water phase. Unlike traditional demulsifiers, the super-hydrophobic porous organic cage modified melamine sponge material prepared by the present invention does not simply form a complex with the stabilizer, but changes the stable structure of the emulsion as a whole. By acting on the oil and water phases at the same time, the stabilizing effect of the stabilizer is quickly destroyed, so that the oil droplets and water droplets in the emulsion can be quickly separated, thereby achieving the same or even better demulsification effect in a short time.
[0127] 9. If Fig. 22 As shown, the super hydrophobic porous organic cage modified melamine sponge material prepared in Example 2 was subjected to the same parameters and conditions as those in the demulsification test of the oil-in-water emulsion without stabilizer, and the demulsification experiment was repeated 15 times, and the water contact angle of Example 5 after repeated use was measured;
[0128] according to Fig. 22 The test results show that after being reused for 15 times, the water contact angle of Example 2 can still reach 132.6°, showing obvious hydrophobicity and excellent reusability. The reason is that the structure of the superhydrophobic porous organic cage modified melamine sponge is stable. The organic cage compound may be attached to the porous skeleton surface of the sponge through physical adsorption, and the organic cage may interact with the sponge skeleton through intermolecular forces (such as van der Waals forces); and some active groups remaining on the aldehyde-modified calix[4]arene (such as unreacted aldehyde or hydroxyl groups) may further react with functional groups such as amino groups on the melamine sponge to form covalent bonds; through the synergistic effect of physical adsorption and chemical bonding, the organic cage compound can be stably and firmly loaded on the melamine sponge skeleton, so that it can still maintain good performance during multiple uses.
[0129] 10. Fig.23 As shown, the super hydrophobic porous organic cage modified melamine sponge material prepared in Example 2 was subjected to a compression test, and the appearance changes of Example 2 before and after compression were compared after continuous compression and pressing for 50 times;
[0130] according to Fig.23It can be seen from the test results that the super-hydrophobic porous organic cage modified melamine sponge material prepared in Example 2 has basically no obvious change in appearance after the compression test, which means that its elastic properties are not significantly affected. It can be seen that the super-hydrophobic porous organic cage modified melamine sponge material not only has good hydrophobicity, but also has stable elastic properties and excellent mechanical stability, which makes its application in actual production and life more convenient and has a wider range of applications, and can better cope with various possible external force situations.
[0131] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention and falling within the scope of protection of the present invention.
Claims
1. A method for preparing a super-hydrophobic porous organic cage-modified melamine sponge material, characterized in that: The following steps are involved: Step (1), preparing a super-hydrophobic porous organic cage precursor solution; The aldehyde-modified calix[4]arene and 2,2'-bis(trifluoromethyl)-[1,1'-biphenyl]-4,4'-diamine are mixed, N-methyl-2-pyrrolidone, chlorobenzene and methanol are added, and ultrasonic treatment is performed. After the treatment, a superhydrophobic porous organic cage precursor solution is obtained; wherein the molar ratio of aldehyde-modified calix[4]arene to 2,2'-bis(trifluoromethyl)-[1,1'-biphenyl]-4,4'-diamine is 1:2-3; Step (2), preparing a pretreated melamine sponge; The melamine sponge is cut into blocks, placed in deionized water, and subjected to ultrasonic treatment. After the treatment, the block is transferred to ultrapure water, and subjected to ultrasonic treatment again. After the treatment, the block is taken out, squeezed, and dried to obtain a pretreated melamine sponge. Step (3), preparing a super-hydrophobic porous organic cage-modified melamine sponge material; The pretreated melamine sponge is immersed in a super-hydrophobic porous organic cage precursor solution to undergo a solvent thermal reaction, and after the reaction is completed, the solution is purified to obtain a super-hydrophobic porous organic cage modified melamine sponge material; The conditions of the solvent thermal reaction are: reacting at a temperature of 60-90° C. for 10-24 hours.
2. The method for preparing a super-hydrophobic porous organic cage-modified melamine sponge material according to claim 1, characterized in that: In the step (1), the volume ratio of N-methyl-2-pyrrolidone, chlorobenzene and methanol is 2:1:1-2.
3. The method for preparing a super-hydrophobic porous organic cage-modified melamine sponge material according to claim 1, characterized in that: In the step (1), the ultrasonic treatment time is 5-20 min.
4. The method for preparing a super-hydrophobic porous organic cage-modified melamine sponge material according to claim 1, characterized in that: In the step (2), the ultrasonic treatment time is 10-20 minutes; the ultrasonic treatment conditions are as follows: ultrasonic treatment is repeated 1-2 times, each time for 10-20 minutes.
5. The method for preparing a super-hydrophobic porous organic cage-modified melamine sponge material according to claim 1, characterized in that: In the step (3), the solid-to-liquid ratio of the pretreated melamine sponge to the super-hydrophobic porous organic cage precursor solution is 1:1-3.
6. A super-hydrophobic porous organic cage-modified melamine sponge material, characterized in that: The super-hydrophobic porous organic cage-modified melamine sponge material is prepared by the preparation method of any one of claims 1 to 5.
7. Application of a super-hydrophobic porous organic cage-modified melamine sponge material in demulsification of water-in-oil emulsions, characterized in that: The super-hydrophobic porous organic cage-modified melamine sponge material according to claim 6 is used.
Citation Information
Patent Citations
Organic cage skeleton synthesized based on Yamamoto coupling reaction, preparation method and application in oil-water separation
CN115926081A